Pelvic floor muscle training and adjunctive therapies for the treatment of stress urinary incontinence in women: a systematic review - Neumann Patricia B; Grimmer Karen A; Deenadayalan Yamini (BMC, 2006)
Abstract Background Stress urinary incontinence (SUI) is a prevalent and costly condition which may be treated surgically or by physical therapy. The aim of this review was to systematically assess the literature and present the best available evidence for the efficacy and effectiveness of pelvic floor muscle training (PFMT) performed alone and together with adjunctive therapies (eg biofeedback, electrical stimulation, vaginal cones) for the treatment of female SUI. Methods All major electronic sources of relevant information were systematically searched to identify peer-reviewed English language abstracts or papers published between 1995 and 2005. Randomised controlled trials (RCTs) and other study designs eg non-randomised trials, cohort studies, case series, were considered for this review in order to source all the available evidence relevant to clinical practice. Studies of adult women with a urodynamic or clinical diagnosis of SUI were eligible for inclusion. Excluded were studies of women who were pregnant, immediately post-partum or with a diagnosis of mixed or urge incontinence. Studies with a PFMT protocol alone and in combination with adjunctive physical therapies were considered. Two independent reviewers assessed the eligibility of each study, its level of evidence and the methodological quality. Due to the heterogeneity of study designs, the results are presented in narrative format. Results Twenty four studies, including 17 RCTs and seven non-RCTs, met the inclusion criteria. The methodological quality of the studies varied but lower quality scores did not necessarily indicate studies from lower levels of evidence. This review found consistent evidence from a number of high quality RCTs that PFMT alone and in combination with adjunctive therapies is effective treatment for women with SUI with rates of 'cure' and 'cure/improvement' up to 73% and 97% respectively. The contribution of adjunctive therapies is unclear and there is limited evidence about treatment outcomes in primary care settings. Conclusion There is strong evidence for the efficacy of physical therapy for the treatment for SUI in women but further high quality studies are needed to evaluate the optimal treatment programs and training protocols in subgroups of women and their effectiveness in clinical practice.